2023
DOI: 10.1371/journal.pntd.0010384
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization and placental pathology of mpox infection in hospitalized patients in the Democratic Republic of the Congo

Abstract: We describe the results of a prospective observational study of the clinical natural history of human monkeypox (mpox) virus (MPXV) infections at the remote L’Hopital General de Reference de Kole (Kole hospital), the rainforest of the Congo River basin of the Democratic Republic of the Congo (DRC) from March 2007 until August 2011. The research was conducted jointly by the Institute National de Recherche Biomedical (INRB) and the US Army Medical Research Institute of Infectious Diseases (USAMRIID). The Kole ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Although this figure was generated from a single study in DR Congo, the four pregnant women in that investigation were not pre-selected and, with the exception of concomitant malaria in one woman, had no significant obstetrical co-morbidities. Their pregnancies culminated in two miscarriages, one stillborn fetus with confirmed infection and Congenital Mpox Syndrome, and one live birth [ 31 , 32 , 34 ]. This should not be surprising, as mpox Clade I has the highest case fatality rate of all mpox clades among non-pregnant individuals, between 10 and 15%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this figure was generated from a single study in DR Congo, the four pregnant women in that investigation were not pre-selected and, with the exception of concomitant malaria in one woman, had no significant obstetrical co-morbidities. Their pregnancies culminated in two miscarriages, one stillborn fetus with confirmed infection and Congenital Mpox Syndrome, and one live birth [ 31 , 32 , 34 ]. This should not be surprising, as mpox Clade I has the highest case fatality rate of all mpox clades among non-pregnant individuals, between 10 and 15%.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the natural history of mpox in an endemic region, the Kole Human Monkeypox Infection Study was performed in the Sankuru Province of DR Congo from March 2007 to July 2011 [ 31 , 32 ]. A cohort of 222 symptomatic patients, of whom 36% were female, were enrolled at the General Hospital of Kole located in a remote town in a region of tropical rainforest where mpox is endemic.…”
Section: Pregnancy With Clade I Mpox Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bridging data from NHPs to humans is contingent upon several hypotheses. First, the experimental model of mpox infection in NHPs is more severe than in humans, with an extensive and prolonged viremia in all animals, compared to the transient and low-level viremia generally observed in humans [ 4 , 6 , 7 ]. Additionally, the NHP model suggested that mpox infection could modify tecovirimat PK, requiring drug exposure analysis in clinical studies [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the 2022 outbreak, mpox has been predominantly reported among men who have sex with men [ 1 ]. Little data are available on the natural history of mpox infection, and findings rely on scarce samplings from small cohorts [ 4 6 ]. In a study conducted in Spain, 77 individuals were enrolled shortly after symptom onset and followed until viral clearance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%